Jane Sandanski i makedonskoto osloboditelno delo : zbornik od nauçniot sobir po povod 90 godini od ubistvoto na Jane Sandanski odrjan vo Skopje na 20 i 21 oktomvri 2005 godina = Jane Sandanski and the Macedonian liberation movement : proceedings of the scientific meeting on the occasion of the 90th anniversary of the assassination of Jane Sandanski held in Skopje on 20th and 21st October 2005 (Skopje)
340 s.